Combined Use of Clips and Nylon Snare (“Tulip-Bundle”) as a Rescue Endoscopic Bleeding Control in a Mallory-Weiss Syndrome - Hrvoje Ivekovic; Bojana Radulovic; Suzana Jankovic; Pave Markos; Nadan Rustemovic (Case Reports in Gastrointestinal Medicine)
Mallory-Weiss syndrome (MWS) accounts for 6–14% of all cases of upper gastrointestinal bleeding. Prognosis of patients with MWS is generally good, with a benign course and rare recurrence of bleeding. However, no strict recommendations exist in regard to the mode of action after a failure of primary endoscopic hemostasis. We report a case of an 83-year-old male with MWS and rebleeding after the initial endoscopic treatment with epinephrine and clips. The final endoscopic control of bleeding was achieved by a combined application of clips and a nylon snare in a “tulip-bundle” fashion. The patient had an uneventful postprocedural clinical course and was discharged from the hospital five days later. To the best of our knowledge, this is the first case report showing the “tulip-bundle” technique as a rescue endoscopic bleeding control in the esophagus.